Video annotation and navigation on mobile devices - Cunha, Bruna C. R.; Pedrosa, Diogo de Carvalho; Goularte, Rudinei; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The growing ease of capturing and playing back videos using mobile devices demands the investigation of alternatives for improving the user experience, for instance by taking advantage of the expanding culture of end-user content generation. Advances in terms of end-user media capture and media combination aim at enriching and facilitating the authoring experience. This work explores the generation of textual annotations on videos played on mobile device: the approach is to offer an application that allows associating annotations to a navigation line decorated with frames that are representative of the points of interest. The aims is to improve the user experience of video annotation by allowing users to to find interesting points intuitively. Experiments with users identified of new issues, even though the application was considered easy to use.